2017
DOI: 10.15644/asc51/2/2
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Orthodontic Brackets Bonded to Zirconium Crowns

Abstract: BackgroundAn increasing demand for esthetic restorations has resulted in an increased use of all-ceramic restorations, such as zirconium. However, one of the challenges the orthodontist must be willing to face is how to increase bond strength between the brackets and various ceramic restorations.Bond strength can beaffected bybracket type, by the material that bracketsaremade of, and their base surface design or retention mode.​Aim: of this study was to perform a comparative analysis of the shear bond strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…According to numerous studies ( 4 , 6 , 13 , 24 , 25 ), the bond strength of ceramic brackets is higher than the strength of metallic brackets. But, our results indicate that this doesn’t occur at orthodontic brackets bonded to zirconia restorations, and this is in accordance with a study previously reported by Mehmeti et al (2017) ( 27 ), where metallic brackets, in comparison with ceramic brackets, bond better with zirconia restorations. This might be because of the base surface design of metallic brackets, producing a better mechanical coupling with zirconia ceramic substrate.…”
Section: Discussionsupporting
confidence: 93%
“…According to numerous studies ( 4 , 6 , 13 , 24 , 25 ), the bond strength of ceramic brackets is higher than the strength of metallic brackets. But, our results indicate that this doesn’t occur at orthodontic brackets bonded to zirconia restorations, and this is in accordance with a study previously reported by Mehmeti et al (2017) ( 27 ), where metallic brackets, in comparison with ceramic brackets, bond better with zirconia restorations. This might be because of the base surface design of metallic brackets, producing a better mechanical coupling with zirconia ceramic substrate.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the samples that were given metal brackets displayed greater shear strength, and a statistically significant difference was indeed found between the metal bracket group and ceramic bracket group. Our finding matches that of the study by Mehmeti et al 19 but contradicts the article by García-Sanz et al 17 This may be due to the design of the metal bracket's base surface, that is, to an uneven surface that creates better mechanical retention compared with ceramic brackets. It would seem that the brackets' mechanical bond to zirconia is stronger than their chemical bond.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies have shown that ceramic brackets are recommended for surfaces like zirconia ahead of metal brackets, 17 yet a recent study has claimed the opposite, finding that metal brackets seemed to adhere more strongly to zirconia surfaces because of their better base surface design and their method of retention. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding of orthodontic brackets directly to the surfaces of ceramic material have shown a high degree failure rate when compared to enamel surface bonding. 4 Therefore, increasing the bond strength between the orthodontic brackets and various types of all-ceramic materials is one of the challenges that orthodontist has to deal with.…”
Section: Introductionmentioning
confidence: 99%